Kampus Mengajar: Developing Literacy and Numeracy Skills of Elementary School Students - Iis Holisin; Shoffan Shoffa (Vygotsky: Jurnal Pendidikan Matematika dan Matematika, 2023)
This research aims to determine the implementation of the Teaching Campus as an effort to grow the literacy ability of elementary school students. The method used is descriptive with a qualitative approach. The subjects of the research consisted of students of SD Budi Yakin Surabaya and students of SDN Langkap Madura. Data were collected using questionnaires, interviews, and documentation techniques. The results showed that students' literacy and numeracy skills have grown and developed. This can be seen from the increased understanding of the material learned, students can retell their reading results well. Students' dependence on teachers when working on LKS is reduced. The recommendation for campuses is that campuses must be able to prepare students' abilities as well as possible so that campus teaching programs provide benefits to schools.